A comparative study of venture capital performance in the US and Europe - Xiaoqing Eleanor Xu (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
For the past fifty years in the United States, venture capital (VC) has provided initial funding to innovative entrepreneurial enterprises, while the European venture capital industry has only really emerged over the past decade. Using quarterly data from 1993 to 2003, this paper examines and compares the return and risk performance of venture capital funds in US and Europe. Several results are noteworthy. First, pooled venture capital returns in US and Europe are 3.273% and 0.765% (on a quarterly basis) above the CAPM market risk-adjusted returns, respectively. Second, US venture capital fund performance dominates that of Europe in all measures: mean return, total-risk adjusted return, and market-risk adjusted return. Third, the linkage between US VC fund performance and the US stock market is much stronger than the co-movement between the European VC and European stock market. Finally, the introduction of Euro.NM in 1997 has substantially enhanced the relationship between the venture capital and stock market performance in Europe.
Keywords: 650